2010
DOI: 10.1111/j.1600-0501.2009.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone augmentation after soft‐tissue expansion using hydrogel expanders: effects on microcirculation and osseointegration

Abstract: Pre-augmentation soft-tissue expansion with hydrogel expanders leads to higher functional microvessel density in the tissue above the augmentation material and thus, to more rapid osseointegration. The use of hydrogel expanders appears to increase the probability of success, especially of pre-implant bone augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 26 publications
3
23
0
4
Order By: Relevance
“…In another in vivo study on rats, von See et al. () reported a higher density of micro‐vessels in the soft tissue surrounding the augmentation material when pre‐augmentation soft tissue expansion was utilised, in comparison with grafted area without a prior soft tissue expansion. This was in agreement with early studies which confirmed an increase in the vascularity of the expanded tissues.…”
Section: Effect Of Soft Tissue Expanders On Micro‐circulation and Sofmentioning
confidence: 99%
See 2 more Smart Citations
“…In another in vivo study on rats, von See et al. () reported a higher density of micro‐vessels in the soft tissue surrounding the augmentation material when pre‐augmentation soft tissue expansion was utilised, in comparison with grafted area without a prior soft tissue expansion. This was in agreement with early studies which confirmed an increase in the vascularity of the expanded tissues.…”
Section: Effect Of Soft Tissue Expanders On Micro‐circulation and Sofmentioning
confidence: 99%
“…Complete osseo‐integration of the bone graft was possible when the mucosal perfusion around the augmentation area was not compromised (von See et al. ). High vessel density of soft tissues seems to play a role in blood supply to the underlying bone (Chanavaz ).…”
Section: Effect Of Soft Tissue Expanders On Micro‐circulation and Sofmentioning
confidence: 99%
See 1 more Smart Citation
“…Future improvements of the coating could include a filler material, such as a hydrogel, that could expand and compress within the knit coating, providing an even greater level of gap coverage to encourage bone in-growth. [28-30] Such a hydrogel could also serve as a depot to deliver bioactive factors to promote osteogenesis and inhibit bacterial infection. [31, 32] Alternatively, much like drug-eluting stents, the nitinol wire could be coated with drugs, small molecules, or peptides that encourage osteogenesis and provide protection against bacterial infection.…”
Section: Challenges and Potential Solutions For Osseointegrationmentioning
confidence: 99%
“…In the second study, our laboratory implanted two left/right implants (6 mm diameter, 2 mm height) per rat within screw-immobilized polypropylene cassettes [17]. Though less influential to our design, others have used subperiosteal pockets [7, 2730], non-immobilized rings [6, 31], and groove [8, 32] or screw immobilization [3335]. Our new model has the advantage of matching the dimensions of the rat critical-sized calvarial defect (8 mm diameter) [36] allowing scaffolds to be tested directly for bone augmentation without repeating in vitro characterization.…”
Section: Discussionmentioning
confidence: 99%